A Holistic Viewpoint for Selecting the Vertical Haulage System – Shafts and Conveyors - R M. Krek (The Australasian Institute of Mining and Metallurgy, 2014)
The haulage system used to convey ore from an underground mine to a surface stockpile at the mine process plant is a vital component of the mine’s overall infrastructure and economic viability. The system selected has a significant impact on the set-up of the mine and the access to the underground mine. In turn, the set-up of the mine and the access to the underground mine have a significant impact on the system.A number of haulage technologies are available to transfer the ore from the underground workings to the surface stockpile, including hoists, conveyors, rail and trucks.This paper focuses on the shaft hoisting and inclined conveyor haulage technologies. These technologies have been used consistently to deliver ore from at depth and/or at high tonnage. Previous reviews of the appropriate vertical haulage systems have nominally been restricted to the respective systems only, with no consideration for any other scope or issues that may affect the selection. The selection of the appropriate vertical haulage system, whether shaft hoisting or inclined conveying, needs to consider numerous key factors.CITATION:Krek, R M and Northcote, A E A, 2014. A holistic viewpoint for selecting the vertical haulage system – shafts and conveyors, in Proceedings 12th AusIMM Underground Operators’ Conference 2014 , pp 289–296 (The Australasian Institute of Mining and Metallurgy: Melbourne).